Respuesta :
Answer:
[tex](-1, 3)[/tex]
Step-by-step explanation:
We have two equations:
[tex]2x+y=1\\3x-y=-6[/tex]
Adding the two linear equations:
[tex](2x+3x)+(y-y)=1+(-6)[/tex]
Simplifying
[tex]5x+0y=1-6[/tex]
[tex]5x=-5\\[/tex]
Clearing for [tex]x[/tex]:
[tex]x=\frac{-5}{5} \\x=-1[/tex]
Now we substitute this value of [tex]x[/tex] in either of the two initial equations to find the value of [tex]y[/tex], Substituting in the first one:
[tex]2x+y=1\\2(-1)+y=1\\-2+y=1\\y=1+2\\y=3[/tex]
the answer is [tex](-1, 3)[/tex] because [tex]x=-1[/tex] and [tex]y=3[/tex]